Deradikalisasi Kaum Remaja dalam Membendung Radikalisme Media Sosial - Mutrofin Mutrofin; Ahmad Kharis (Jurnal Sosiologi Agama, 2020)
The emergence of information media has resulted in a massive revolution in the pattern of relations between people as individuals and groups. This changes the information media as a realm of upheaval in the propaganda community that has an interest, including as a propagator of radical ideology. Deradicalization program as a strategic action which is based on conceptual understanding to deal with issues related to the development of ideologies and axis of radicalism is very important to be implemented in adolescents in this millennial era. Through this paper the author wants to discuss efforts to counter radicalism activities among adolescents, especially on social media platforms. By examining issues related to the latest radicalism and analyzing literature literacy. The author hopes this article can be useful for deterring radicalism activities, especially on social media.